A global assessment of Echinococcus multilocularis infections in domestic dogs: proposing a framework to overcome past methodological heterogeneity. Issue 5 (April 2021) - Toews, Emilie; Musiani, Marco; Checkley, Sylvia; Visscher, Darcy; Massolo, Alessandro
Graphical abstract: Highlights: Parasitism of Echinococcus multilocularis in dogs is prevalent, but unevenly studied. The most informative true prevalence is rarely estimated in dogs. For dogs, few studies analyse risk factors, despite their potential significance. Rural, untethered dogs used for hunting are more prone to E. multilocularis infection. Future studies should adopt a common framework to estimate prevalence accurately. Abstract: Echinococcus multilocularis, the aetiological agent of human Alveolar Echinococcosis, is transmitted between small mammals and wild or domestic canids. Dogs infected with E. multilocularis as dead-end hosts. Whereas E. multilocularis infections in wild hosts and humans have been well-studied in recent decades, infections in domestic dogs are sparsely reported. This literature review and meta-analysis highlighted gaps in the available data and provided a re-assessment of the global distribution of domestic dog E. multilocularis infections. We found 46 published articles documenting the prevalence of E. multilocularis in domestic dogs from 21 countries across Europe, Asia and North America. Apparent prevalence estimates ranged from 0.00% (0.00–0.33%) in Germany to 55.50% (26.67–81.12%) in China. Most studies were conducted in areas of high human Alveolar Echinococcosis. By accounting for reassessed diagnostic sensitivity and specificity, we estimated true prevalence in a subset of studies, which varied between 0.00% (0.00–12.42%) and 41.09% (21.12–65.81%), as these true prevalence estimates were seldom reported in the articles themselves. Articles also showed a heavy emphasis on rural dogs, dismissing urban ones, which is concerning due to the role urbanisation plays in the transmission of zoonotic diseases, especially those utilising pets as definitive hosts. Lastly, population studies on canine Alveolar Echinococcosis were absent, highlighting the relative focus on human rather than animal health. We thus developed a framework for investigating domestic dog E. multilocularis infections and performing risk assessment of dog-associated transmission to fill the gaps found in the literature.